Exploring the role of green finance in wind power development: using the nonparametric model - Xu, Bin; Lin, Boqiang (Frontiers in Sustainable Energy Policy, 2024)
In the context of the "dual carbon" strategy, how to leverage green finance to promote China's wind power industry is a hot topic. Unlike existing literature, this article uses a nonparametric additive model to investigate the impact and mechanism of green finance on wind power development. Research has found that green finance has an inverted U-shaped nonlinear impact on wind power development, indicating that green finance has a more prominent contribution to the wind power industry in the early stages. Further mechanism research indicates that green finance affects the wind power industry through foreign direct investment and green technology innovation. Specifically, with the relaxation of foreign direct investment conditions in the energy sector, the role of foreign direct investment in promoting the wind power industry more prominent in the later stages. In the early stages, government support was greater, and green technology patents grew rapidly, driving green technology innovation to have a more significant impact on the wind power industry. In addition, the impact of fiscal decentralization, wind power prices, and environmental regulations on the wind power industry also exhibits significant nonlinear characteristics. This article helps to comprehensively understand the mechanism and impact of green finance on wind power development, and provides a reliable basis for optimizing green finance policy and effectively promoting wind power.